The flora of pine forests of the vicinity of Hrafske village (Vovchansk District, Kharkiv Region) - H. Kazarinova; O. Skryaga; G. Bondarenko (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія, 2021)
The article presents the results of a study of the flora of pine forests in the vicinities of the villages Hrafske, Verkhnia Pysarivka, and Symonivka of the Vovchansk District of the Kharkiv Region. The flora of the investigated area includes at least 120 species of vascular plants of 47 families, five classes, and four divisions. The richest in the flora are the families Asteraceae (22 species; 18.3%), Poaceae (13 species; 10.8%), and Caryophyllaceae (10 species; 8.3%) that are characteristic of the pine forests of the Kharkiv Region. The presence of Crassulaceae (5 species; 4.2%) at the fifth position in the spectrum of dominating families is due to anthropogenic impact on the vegetation of the study area.  Analysis of the flora ecological structure by three main abiotic factors (soil water regime, total salt regime, and light) has shown the typical conditions of the valley forests of the Kharkiv Region with a predominance of mesophytic and submesophytic (84 species; 70%), semieutrophic (64 species; 52.9%) and subheliophytic (88 species; 72.7%) groups of plants. In the coenotic structure of the flora of studied forests, the forest (38 species; 31.4%) and ruderal (37 species; 30.6%) fractions were the leading ones, while the third position was occupied by the psammophytic species (22; 18.2%). A high number of weeds in the flora composition is explained by urbanization. Fractional analysis of the flora has shown a predominance of native species (90; 75%), mainly apophytes (47; 39.2%), adapted to growing in disturbed habitats. The adventive fraction includes 30 species (25%), among which kenophytes and xenophytes predominate. Localities of three rare species (Dryopteris carthusiana (Vill.) H.P. Fuch, Jurinea charkoviensis Klok., and Viburnum opulus (L.) Opiz.) were identified, which indicated conservation value of the study area. An index of the flora synanthropization (64.5%) is quite high due to ruderal species adapted to disturbed habitats. The studied valley forests are under anthropic pressure caused by nearby settlements via littering and deforestation, which results in flora impoverishment and the spread of alien plant species. Therefore, the forests in question require further monitoring.